Kejadian Kelainan Vertebra Ikan Nila (Oreochromis niloticus) pada Media Penetasan Salinitas yang Berbeda [Vertebrae Malformation Tilapia Fish (Oreochromis niloticus) on Different Media Hatching Saline] - Lailatul Lutfiyah; Rr Juni Triastuti; Endang Dewi Masithah; Win Darmanto (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Tilapia fish belonged to the euryhaline fish, which has wide range tolerance in salinity (freshwater euryhaline fish has salinity tolerance >8 ppt). Incidence of fish skeletal abnormalities could be the response of the environment influence such as salinity, temperature and hypoxia. This research uses five treatments : 0,5 10, 15, 20 ppt. The results showed that the highest abnormalities found on the treatment of 15 ppt and 20 ppt, while the lowest for the treatment of abnormalities of 10 ppt. The best result to be used in the brackish nila aquaculture is 10-15 ppt in salinity.